Lectures et relectures de la non indépendance cubaine : l’île révolutionnaire et son passé de Très Fidèle (1790-1830) - Romy Sánchez (Centre de Recherches sur les Mondes Américains, 2008)
This article aims at establishing a link between the idea of insular teleology in the Cuban historiography and the lack of historicity that appears to characterize the so-called period of the "American Independences" as far as Cuba is concerned. The main goal of this work is to understand why Cuba was not that anti-Spanish rebel bastion between 1808 and 1825 although the Castro's Revolution and its uses of the country's history turned this moment -which might actually not be one -into the moment of confiscated independence. Using the archives of an insular society -certainly more heterogeneous than the representation conveyed by the "colonial" stereotypes -, it is possible to question the dissonances between the circulating ideas stemming from the Havana case study during that period of time and the relatively fixed discourse that the Revolution and its historiography tried to impose on these years, too little studied int the Cuban context. Would then the way out of insular teleology mean taking a step towards accepting the idea of a period of non-independence?